6(12-m)=6(2m)

Simple and best practice solution for 6(12-m)=6(2m) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(12-m)=6(2m) equation:



6(12-m)=6(2m)
We move all terms to the left:
6(12-m)-(6(2m))=0
determiningTheFunctionDomain 6(12-m)-62m=0
We add all the numbers together, and all the variables
6(-1m+12)-62m=0
We add all the numbers together, and all the variables
-62m+6(-1m+12)=0
We multiply parentheses
-62m-6m+72=0
We add all the numbers together, and all the variables
-68m+72=0
We move all terms containing m to the left, all other terms to the right
-68m=-72
m=-72/-68
m=1+1/17

See similar equations:

| 0.7-5.92=0.34r+6.76 | | 5x+8+3x-14=90 | | 3r+10=4r+5 | | 3p+5p=4p | | 14x+7-13x=5 | | 6x+7-7x=-2 | | 6(v-4)-8v=-36 | | -12s-7=5 | | 5x-7=11x-53 | | 4(-8k+7)=252 | | .5(5x+12)=-3 | | 27=25-3y | | 25x-100=30x | | 4(3n-2)=16n | | -2=-2n | | 12x+42=-8.5x-40 | | 2x+4+4x+23=75 | | 6(x-1)=-7(x-7)+2x | | 5x-34+104=180 | | (3x)=(4x+110) | | -2d−7=-3d+2 | | 8t-18=14 | | (x/4)=2 | | -5(v-2)=2(4v+6)-11v | | 1/3(9x-24)=x+5+2x | | 13x+9x-10=32 | | 10x+-50=30 | | 19=2z-2z | | 4n+27=180 | | 8t+-18=14 | | (7x+24)+(7x-26)=90 | | 0.35(x-0.6)=0.2(x+1.2) |

Equations solver categories